Inisiatif Pendidikan Unggul: Program Muhadatsah Bahasa Arab di MA Unggulan K.H. ABD Wahab Hasbulloh - Shobirin, Mochammad Syafiuddin; Arrosyid, Mokhammad Iqbal; Khotimah, Husnul (ISLAMIKA, 2024)
The research investigates the effectiveness of the Arabic Language Muhadatsah Program at the Leading Islamic High School (Madrasah Aliyah) KH. ABD. Wahab Hasbulloh as a prominent educational initiative. The research method involves a comprehensive analysis of participants and the evaluation of the learning tools utilized in the program. By integrating innovative teaching methods, such as Arabic language dialogue simulations and enhancing speaking skills, the study focuses on measuring the improvement of students' Arabic language skills. The research findings highlight a significant enhancement in Arabic language learning, particularly in the muhadatsah or speaking skills aspect. These results provide important contributions to understanding the effectiveness of the prominent Arabic language learning program at educational institutions, specifically at MA Unggulan K.H. ABD Wahab Hasbulloh, Leading Islamic High School, offering evidence and recommendations for ongoing curriculum development and teaching quality enhancement efforts. This abstract underscores the crucial value of skill-focused programs and a focus on foreign educational excellence.